2008
DOI: 10.1007/s00586-008-0833-4
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between radiographic shoulder balance and cosmetic shoulder balance in adolescent idiopathic scoliosis patients with double thoracic curve

Abstract: Shoulder balance is one of the key components to the body deformity in adolescent idiopathic scoliosis (AIS) patients with double thoracic curve and shoulder cosmesis plays an important role in patients' satisfaction of surgical outcomes. Up to now, only radiographic parameters were used to evaluate the shoulder balance in literatures; no corresponding cosmetic parameters have been developed to evaluate the cosmetic shoulder balance. Meanwhile, we often confronted that perfect radiographic shoulder balance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 27 publications
3
75
0
3
Order By: Relevance
“…Mac-Thiong et al [4] found similar relationships in AIS with severe scoliosis. A number of articles relate trunk rotation with the Cobb angle (Goldberg et al [2] and Amendt et al [31]) and shoulder cosmesis (Qiu et al [32]), but none reported any correlation with pelvic geometry. Gum et al [10] found only a suggestive correlation of 0.3259 (p = 0.0736) between the largest Cobb angle and left/right pelvic width ratios for the AIS Lenke 1A1 thoracic sub-group.…”
Section: Discussionmentioning
confidence: 99%
“…Mac-Thiong et al [4] found similar relationships in AIS with severe scoliosis. A number of articles relate trunk rotation with the Cobb angle (Goldberg et al [2] and Amendt et al [31]) and shoulder cosmesis (Qiu et al [32]), but none reported any correlation with pelvic geometry. Gum et al [10] found only a suggestive correlation of 0.3259 (p = 0.0736) between the largest Cobb angle and left/right pelvic width ratios for the AIS Lenke 1A1 thoracic sub-group.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that contribute to the clinical aspects of shoulder deformity are not thoroughly understood. Attempts to evaluate shoulder balance via radiographic parameters are met with significant challenges due to generally less than moderate correlation between radiographic and clinical parameters [5]. Clinicians often focus on the appearance of the shoulders when viewed posteriorly, although patients may focus on anterior shoulder balance.…”
Section: Discussionmentioning
confidence: 99%
“…1). Main thoracic Cobb angle, T1 tilt, and FRA were previously described measures by Bago et al and Qiu et al [5,10]. T1 tilt is the angle between the line through the superior endplate of T1 and a horizontal line.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations